L'obra atribuïda al pare Mulet: comèdies i versos. - JOSEP ESCARTÍ, VICENT (Scripta)
The existence of Francesc Mulet (1624-1675) and his literary works seem to have generated doubts as early as the 19th century. The lack of irrefutable evidence regarding his authorship of some of the compositions attributed to him, and especially his plays, has only added to the existing uncertainty. In this work, we attempt to examine the reception of Mulet's attributed works over time.